Regulatory Affairs 101: Introduction to Investigational New Drug Applications and Clinical Trial Applications - Davy Chiodin; Erica M. Cox; Anita V. Edmund; Erica Kratz; Sarah H. Lockwood (Wiley, 2019)
Testing novel drugs on fellow human beings is fraught with potential ethical concerns; however, developing drugs to treat the wide spectrum of human diseases and disorders is a moral imperative. How do we best navigate the balance between protecting the individual vs. the greater good? Global government regulatory bodies are accountable for ensuring that medical experiments on human subjects are appropriately justified and subject to close oversight. In this article, we focus on two major global health authorities, the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA), and the path to legally treating humans with new investigational products.